(untitled) (Journal of National Institute of Neurosciences Bangladesh, 2018)
Background: Clinical profiles of the teenage pregnancy are diffident from the adult pregnancy. Objective: The purpose of the present study was to compare the clinical profiles of teenage and adult pregnancy. Methodology: This comparative cross sectional study was conducted in the Department of Obstetrics and Gynecology at Dhaka Medical College & Hospital, Dhaka, Bangladesh and Sir Salimullah Medical College & Mitford Hospital, Dhaka, Bangladesh from April to July 1999 for a period of four (4) months. The teenage mothers with the age group of 11 to 19 years who were admitted in the study period were selected as group A and pregnant women with the age group of more than 19 years were selected as group B. All the clinical profiles of these two groups were recorded after admission of these pregnant women. Result: Among the primigravid patients, 50 cases with the age group 11 to 19 years were in the group A and 50 patients with the age group more than 19 years were in group B were selected. Among teens, 68 percent have no antenatal cheek-up. Moderate anaemia was more frequently found in the group A than group B which was 14(28.0%) and 9(18.0%) cases respectively. Moderate oedema was more frequently found in the group A than group B which was 16(32.0%) and 12(24.0%) cases respectively. In teenage group 32(64.0%) cases were without hypertension, whereas 44(88.0%) cases were in adult group. Conclusion: In conclusion anaemia and oedema are more commonly found in the teen pregnancy. Journal of National Institute of Neurosciences Bangladesh, 2018;4(1): 8-11